The New Trend in Digital School of Tafsīr: Qur’an Journaling and the Reconfiguration of Religious Authority on @Aisharizqy’s Instagram - Farahdiba, Ani Nabila (Journal of Ushuluddin and Islamic Thought, 2024)
This paper aims to analyse the practice of Qur’an Journaling as a new tool that serves as a medium for learning tafsīr and disseminating religious content among the younger generation. This topic is worth reviewing due to the observed transformation of religious authority through social media, which has shifted traditional figures such as scholars and clerics to digital influencers, significantly impacting how audiences engage with interpretations. This descriptive-analytical study sources its data from online media, specifically Qur’an journaling content posted by the Instagram account @aisharizqy, making this research a form of virtual ethnography. Roger Fidler’s media morphosis approach is used to identify three critical concepts: co-evolution, convergence, and complexity. This approach is employed to explore further the process of media shifts concerning tafsīr references over time. The findings indicate that Qur’an Journaling is a manifestation of the transformation of the school (madrasah) of tafsīr, combining traditional religious practices with modern technology. Despite the novelty in the form of communicators and media, this practice remains rooted in existing oral and written traditions. Additionally, social media as an online community plays a role in reinforcing an individual’s religious identity through virtual religious symbols. These findings also indicate a contestation and shift in how religious authority is constructed and recognized in the digital era. This shift in authority has implications for the interpretation and citation of tafsīr among Muslims, who rely more on digital sources and social media. This transformation also reflects the emergence of a new phase in tafsīr learning that requires a critical evaluation of the validity and credibility of digital sources in the contemporary era.